Konstantin Stanislavski and Emile Jaques-Dalcroze: historical and pedagogical connections between actor training and music education. Issue 2 (3rd July 2021) - Davidson, Andrew
ABSTRACT: This paper explores the fields of actor training and music education in order to illuminate the historical and pedagogical connections between the work of Konstantin Stanislavski and Emile Jaques-Dalcroze. It identifies historical parallels between their artistic practices, including their dedication to rhythm and polyrhythm. It illustrates the ways in which their pedagogical paths crossed. It analyses the artistic lineage that can be drawn from the work of Jaques-Dalcroze at the Hellerau Institute to the work of Stanislavski at the Moscow Art Theatre. This includes the influence of Dalcroze Eurhythmics on the development of Tempo-Rhythm. The paper considers how aspects of Stanislavskian actor training are reflected in aspects of Dalcrozian music education, including ensemble work, intention and emotion, and the evolution of psychophysical performance. It proposes that there is a correlation between the creative process undertaken by an actor on a play text, known as Active Analysis, and the creative process undertaken by a musician on a compositional score, known as Plastique Animée . Comparing the pedagogical principles of Stanislavski and Jaques-Dalcroze from the author's own perspective as an actor trainer and music educator reveals areas for further research. This paper presents themes that are transferable to artists and educators engaged in continuing professional development.